Electoral Personalization and TikTok Politics: The Transformation of Campaign Strategies in Indonesia's 2024 General Election - Laras Maheswari (Indonesian Political Transformation, 2026)
The rapid expansion of TikTok has transformed political campaigning by prioritizing personalized communication, algorithmic visibility, and emotionally engaging content over conventional forms of electoral mobilization. Indonesia's 2024 General Election offers an important opportunity to examine how digital platforms reshape campaign strategies and voter engagement in one of the world's largest democracies. Although previous research has explored the political impact of social media, limited attention has been devoted to TikTok's unique role in accelerating electoral personalization and redefining political branding. This study investigates how political candidates, campaign teams, and voters utilized TikTok during Indonesia's 2024 election. Using a mixed qualitative approach, the research combines digital content analysis, engagement metrics, interviews with campaign strategists, and discourse analysis of highly viewed political videos. The findings demonstrate that successful campaign strategies increasingly relied on authenticity, entertainment, emotional storytelling, and algorithmic optimization rather than ideological messaging alone. This transformation contributed to greater political accessibility among younger voters but also encouraged personality-centered politics and simplified policy discussions. The article argues that TikTok has become a significant institution within contemporary electoral politics by reshaping political communication, voter behavior, and democratic participation. It contributes to comparative political communication literature by extending debates on platformization, algorithmic governance, and digital campaigning beyond Western democracies. The findings provide practical implications for election management bodies, policymakers, and digital platforms seeking to balance political innovation with electoral fairness, transparency, and democratic accountability.